Enhanced Mortality to Metastatic Bladder Cancer Cell Line MB49 in Vasoactive Intestinal Peptide Gene Knockout Mice - Mirsaidi, Niely; Burns, Matthew P.; McClain, Steve A.; Forsyth, Edward; Li, Jonathan; Dukes, Brittany; Lin, David; Nahvi, Roxanna; Giraldo, Jheison; Patton, Megan; Wang, Ping; Lin, Ke; et al. (Frontiers in Endocrinology, 2017)
To identify if the absence of the Vasoactive Intestinal Peptide (VIP) gene enhances susceptibility to death from metastatic bladder cancer, two strains of mice were injected with MB49 murine bladder cancer cells. The growth and spread of the cancer was measured over a period of 4 weeks in C57BL/6 mice and 5 weeks in VIP knock-out (KO) mice. A Kaplan-Meier plot was constructed to compare control C57BL/6 mice and C57BL/6 mice with MB49 vs. VIP KO controls and VIP KO mice with MB49. The wild type (WT) strain (C57BL/6) contained the VIP gene, while the other strain, VIP knock-out backcrossed to C57BL/6 (VIP KO) did not, and was thus unable to endogenously produce VIP. VIP KO mice had increased mortality compared to C57BL/6 mice at 4 weeks. The number of ulcers between both groups was not statistically significant. In vitro studies indicated that the presence VIP in high doses reduced MB49 cell growth, as well as Macrophage Inhibitory Factor (MIF), a growth factor in bladder cancer cells. These findings support the concept that VIP may attenuate susceptibility to death from bladder cancer, and that it exerts its effect via downregulation of MIF.